Shared PKS Module in Biosynthesis of Synergistic Laxaphycins - Heinilä, Lassi Matti Petteri; Fewer, David P.; Jokela, Jouni Kalevi; Wahlsten, Matti; Jortikka, Anna; Sivonen, Kaarina (Frontiers in Microbiology, 2020)
Cyanobacteria produce a wide range of lipopeptides that exhibit potent membrane-disrupting activities. Laxaphycins consist of two families of structurally distinct macrocyclic lipopeptides that act in a synergistic manner to produce antifungal and antiproliferative activities. Laxaphycins are produced by range of cyanobacteria but their biosynthetic origins remain unclear. Here, we identified the biosynthetic pathways responsible for the biosynthesis of the laxaphycins produced by Scytonema hofmannii PCC 7110. We show that these laxaphycins, called scytocyclamides, are produced by this cyanobacterium and are encoded in a single biosynthetic gene cluster with shared polyketide synthase enzymes initiating two distinct non-ribosomal peptide synthetase pathways. To our knowledge, laxaphycins are the first clearly distinct polyketide synthase and non-ribosomal peptide synthetase hybrid natural products with shared branched biosynthesis. The unusual mechanism of shared enzymes synthesizing two distinct types of products may aid future research in identifying and expressing natural product biosynthetic pathways and in expanding the known biosynthetic logic of this important family of natural products.